The 2010 Meningococcal outbreak in Bahia, Brazil, was caused by 2 different STs belonging to Clonal Complex ST-103 - Ivano Raffaele Victorio de Filippis; Rita de CÃ¡ssia Vilasboas Silva; MÃ¡rcia Cristina Rodrigues Guilam; Rubens Onofre Nodari (Vigilância Sanitária em Debate: Sociedade, Ciência & Tecnologia, 2012)
An outbreak of meningococcal disease in the North-East (NE) region of Brazil with 11 cases and seven deaths was reported in 2009. From the 11 cases, five serogroup C meningococcal strains were isolated, four were classified as belonging to the hypervirulent clonal complex ST-103 (cc103) and one strain was not associated with any clonal complex. DNA sequencing of the genes encoding outer membrane proteins PorA and FetA showed genotype P1.5-1,10-1,36-2;F3-9 for all five strains. cc103 was first detected in the southern region of Brazil in 2007, but not associated with outbreaks. MLST analysis detected three new STs among the isolates, showing the ongoing evolution of cc103 and the need of monitoring its spread in the population.